Nonlinear Real Exchange Rate Behavior: Are the African Currencies Exceptional? - Anoruo, Emmanuel; Liew, Venus Khim-Sen; Elike, Uchenna (EuroJournals Publishing, Inc., 2006)
Upon the discovering of nonlinear behavior of exchange in developed countries, Middle East and Asian regions in the recent literature, whether or not the African region is an exception remains an interesting but unaddressed issue. In this respect, this study demonstrates, via formal linearity test, that all the 13 selected African real exchange rates are also nonlinearly behaved. Further investigation through nonlinear stationary tests reveals that 11 of them are nonlinear stationary. The major implication of these results include: First, that there is a long run cointegration relation between the bilateral nominal exchange rates and their corresponding relative prices thereby validating the long run PPP in the African region. Second, the bilateral nominal exchange rates are mean reverting towards the PPP equilibrium positions. As such relative prices may be regarded as effective tool in evaluating the current alignment or misalignment of African exchange rate and hence forecasting and monitoring their future movements.